MRI Improves 3-Month Outcome Prediction in Mild Traumatic Brain Injury - YUH, ESTHER L. (2012)
OBJECTIVE: To determine the clinical relevance, if any, of traumatic intracranial findings on early head CT and brain MRI to 3-month outcome in mild traumatic brain injury (MTBI) METHODS: 135 MTBI patients evaluated for acute head injury in emergency departments of three Level I Trauma Centers were enrolled prospectively. In addition to admission head CT, early brain MRI was performed 12+/-3.9 days after injury. Univariate and multivariate logistic regression were used to assess for demographic, clinical, socioeconomic, CT, and MRI features that were predictive of Extended Glasgow Outcome Scale (GOS-E) at 3 months post-injury. RESULTS: Twenty-seven percent of MTBI patients with normal admission head CT had abnormal early brain MRI. CT evidence of subarachnoid hemorrhage was associated with a multivariate odds ratio of 3.5 (p=0.01) for poorer 3-month outcome, after adjusting for demographic, clinical, and socioeconomic factors. One or more brain contusions on MRI, and ≥4 foci of hemorrhagic axonal injury on MRI, were each independently associated with poorer 3-month outcome, with multivariate odds ratios of 4.5 (p=0.01) and 3.2 (p=0.03), respectively, after adjusting for head CT findings and demographic, clinical, and socioeconomic factors. INTERPRETATION: In this prospective multicenter observational study, the clinical relevance of abnormal findings on early brain imaging after MTBI is demonstrated. The addition of early CT and MRI markers to a prognostic model based on previously known demographic, clinical, and socioeconomic predictors resulted in a greater than two-fold increase in the explained variance in 3-month GOS-E.